'Taking the wheels off': young people with cognitive impairment in out-of-home care. Issue 6 (2nd November 2019) - Greig, Hannah; McGrath, Andrew; McFarlane, Kath
Abstract : Children with cognitive impairment in out-of-home care (OOHC) are significantly over-represented in the criminal justice system. Little attention has been given to the connection between those with cognitive impairment who also have a care background and how these combined factors are linked to their criminal behaviour. A qualitative study utilising semi-structured interviews with 11 senior strategic officers and service providers to this cohort was conducted with the aim of investigating the views of these professionals and gaining insight into factors contributing to the criminalisation of children with cognitive impairment in OOHC. Five themes were identified using thematic analysis, suggesting that the primary areas of concern are: (a) increased vulnerability, (b) lack of belonging and security, (c) challenges with identification, (d) steering to the criminal justice system and (e) lack of support. These findings have important implications for both policy and practice, which are discussed in full.